Sensor amperométrico a base de nanotubos de carbono e ácido vanílico para determinação simultânea de ácido ascórbico, dopamina e ácido úrico - Silva, Leonardo Vieira da (2013)
Due to the system does not recognize equations and formulas the resumo and abstract can be found in the PDF file.